Kualitas Kehujjahan Hadis (Sahih, Hasan, Dhaif) - Sonia Purba Tambak; Khairani Khairani (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
Hadith is the second source of law after the Qur’an. One of the functions of the hadith is as an interpretation bay which aims to clarify the verses of the Koran. In understanding the law based on hadith, one must know the hujjahan hadith. Hadith seen from the quality of its proof is divided into three, namely authentic hadith, hasan, daif. This research is a library research and is included in the category of qualitative research. The purpose of this paper is to analyze the profanity of hadiths which contain authentic, hasan and daif hadiths. The results of this study indicate that the degree of a hadith has several possibilities, we could say authentic, hasan, or daif. Sahih if it fulfills the five conditions that have been agreed upon by the hadith scholars, hasan if there are a few conditions that are not met, and dha'if if the conditions that are not fulfilled are more than the hadith hasan. The highest blasphemous hadith is authentic hadith, then hasan hadith and the weakest is dhai'if hadith. Keywords: Hadith blasphemy, sahih, hasan, daif